Effect of Fruit Volatiles from Native Host Plants on the Sexual Performance of Anastrepha fraterculus sp. 1 Males - Bachmann, Guillermo Enrique (2023)
Anastrepha fraterculus sp.1 males are sexually stimulated by the aroma of fruit of its native host Psidium guajava (guava). Other hosts, which are exotic to A. fraterculus, do not enhance male sexual behavior. Here we evaluate the effects of fruit volatile exposure on male A. fraterculus sp. 1 sexual performance using other native hosts, under the hypothesis that male improvement derives from a common evolutionary history between A. fraterculus sp. 1 and its native hosts. Four species were evaluated: Eugenia myrcianthes, Juglans australis, Psidium cattleianum, and Acca sellowiana. Guava was used as a positive control. Males were exposed to fruit from 12:00 pm to 4:00 pm, from day 8 to day 11 post-emergence. On day 12, we evaluated their calling behavior and mating success. Both guava and P. cattleianum enhanced calling behavior. Mating success was enhanced only by guava and a trend was found for P. cattleianum. Interestingly, the two hosts belong to the Psidium genus. A volatile analysis is planned to identify the compounds responsible for this phenomenon. The other native fruits did not improve the sexual behavior of males. Implications of our findings in the management of A. fraterculus sp. 1 are discussed.